2015
DOI: 10.1515/zfs-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Prosodische (De-)Kodierung des Informationsstatus im Deutschen

Abstract: Abstract:In a production experiment and two follow-up perception experiments on read German we investigated the relation between givenness (also called information status) and prosody based on a cognitive activation cost model. Previous studies provide evidence that it is the tonal configuration which is important for encoding a referent's degree of givenness and that different types of more or less activated information demand different accent types as linguistic markers. Therefore, we assume that changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 2 publications
1
18
0
Order By: Relevance
“…Well-studied languages such as German exhibit similar probabilistic mappings of different tonal events expressing the same function (e.g. H+!H* and L+H* expressing given referents, Baumann, Röhr & Grice 2015). What makes Tashlhiyt seemingly different from the German case is that it shows a probabilistic association of arguably the same tonal event to different structural units in the utterance.…”
Section: Discrete Variability In Intonationmentioning
confidence: 99%
“…Well-studied languages such as German exhibit similar probabilistic mappings of different tonal events expressing the same function (e.g. H+!H* and L+H* expressing given referents, Baumann, Röhr & Grice 2015). What makes Tashlhiyt seemingly different from the German case is that it shows a probabilistic association of arguably the same tonal event to different structural units in the utterance.…”
Section: Discrete Variability In Intonationmentioning
confidence: 99%
“…More recent work takes such variability into account and provides information as to the statistical distribution of alternative realisations of a given function (e.g. Yoon, 2010 for English; Grice et al, 2017, Baumann, 2006 andBaumann, Röhr, &Grice for German;Cangemi & Grice, 2016 for Italian).…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, the non-significant correlation between scaling and alignment (cf. Figure 7) reflects their status as less prominent than broad focus accents [30,31]. Concerning structural effects, this study revealed that [±voice] of a following consonant has a significant effect on F0 peak alignment in German nuclear falling accents.…”
Section: Discussionmentioning
confidence: 73%